Characterization of AMPA receptors targeted by the climbing fiber transmitter mediating presynaptic inhibition of GABAergic transmission at cerebellar interneuron-Purkinje cell synapses - Satake, S. (2016)
10.1523/JNEUROSCI.4894-05.2006